Responsabilidade penal da pessoa jurídica: a teoria do delito em face da autorresponsabilidade do ente coletivo - Correra, Marcelo Carita (2021)
This essay seeks to analyze the legal liability system of legal entities. The main point is the possibility of crimes committed by legal entities (self-responsibility system). The contrast between the theory of reality and the theory of fiction was examined. The first theory takes the legal entity as a reality, insofar as it actively interacts in society, executing contracts, etc. Therefore, it would not be reasonable to deny the criminal responsibility of the entity that interacts daily in society. The theory of fiction, however, does not recognize the legal entity's capacity for action for criminal purposes, as it is an abstract created by humans and without its own will. The legal model adopted by Brazil takes the determinations of legal positivism and, therefore, requires, for criminal responsibility to exist, as an unavoidable fact, the conduct of a human being. Thus, the conclusion that the legal entity cannot be held liable for crimes cannot be ruled out, as it is not able to practice conduct. The model of heteroresponsibility cannot justify the criminal liability of legal entities because the transmission of criminal liability is unconstitutional. However, it is possible to make criminal liability feasible by adopting the premises of Niklas Luhmann's2 systems theory. The relevant information for the incidence of legal rules, also criminal law, is the communicational activity (which can be practiced by legal entities) and no longer an act or conduct by a human being. This solution is only possible by taking the legal system as an autopoietic system, based on communication. The essential element of the system is this communication. The anthropocentric premise of legal positivism needs to be removed from the legal system